The adaptor protein Miro1 modulates horizontal transfer of mitochondria in mouse melanoma models - Jaromir Novak; Zuzana Nahacka; Gabriela L. Oliveira; Petra Brisudova; Maria Dubisova; Sarka Dvorakova; Sona Miklovicova; Marketa Dalecka; Verena Puttrich; Lenka Grycova; Silvia Magalhaes-Novais; Catarina Mendes Correia; et al. (Cell Reports)
Summary: Recent research has shown that mtDNA-deficient cancer cells (ρ0 cells) acquire mitochondria from tumor stromal cells to restore respiration, facilitating tumor formation. We investigated the role of Miro1, an adaptor protein involved in movement of mitochondria along microtubules, in this phenomenon. Inducible Miro1 knockout (Miro1KO) mice markedly delayed tumor formation after grafting ρ0 cancer cells. Miro1KO mice with fluorescently labeled mitochondria revealed that this delay was due to hindered mitochondrial transfer from the tumor stromal cells to grafted B16 ρ0 cells, which impeded recovery of mitochondrial respiration and tumor growth. Miro1KO led to the perinuclear accumulation of mitochondria and impaired mobility of the mitochondrial network. In vitro experiments revealed decreased association of mitochondria with microtubules, compromising mitochondrial transfer via tunneling nanotubes (TNTs) in mesenchymal stromal cells. Here we show the role of Miro1 in horizontal mitochondrial transfer in mouse melanoma models in vivo and its involvement with TNTs.